Determination Certain Hydroxy Compounds With the use of Ce(IV) Reagent - Shukla, I.C. (Asian Journal of Chemistry, 2010)
In the present work, the use of Ce(IV) reagent viz., ammonium hexanitratocerate (IV) in the determination of various hydroxy compounds has been described.